Ceriantharia (Cnidaria) of the world: An annotated catalogue and key to species - Stampar, Sérgio N. [UNESP]; Reimer, James D.; Maronna, Maximiliano M.; Lopes, Celine S. S. [UNESP]; Ceriello, Hellen [UNESP]; Santos, Thais B. [UNESP]; Acuña, Fabián H.; Morandini, André C. (Pensoft Publishers, 2020)
The diversity of Ceriantharia is known from studies formally describing species from the late 18th Century onwards. However, no nomenclators including a list and discussion of all valid species have been produced since a list discussed by Carlgren in 1912. The present nomenclator presents a complete list of adult species of Ceriantharia of the World, including a discussion on each species. It includes the three families (Arachnactidae, Botrucnidiferidae, Cerianthidae) and the currently accepted 54 species based on their adult form. This study serves as a presentation of the “state-of-the-art” list of species of Ceriantharia, and includes a species identification key to support taxonomic identification. Additional in-depth species-byspecies investigations for almost all cerianthid species is still needed, as the information available for most of these species is quite superficial.
Keywords: Cnidaria; Families; Genera; Identification key; Tube-dwelling anemones